Reaksi Pasar Atas Pengumuman Dividen (Studi Pada Emiten Yang Terdaftar Di Jakarta Islamic Index) - Ari Widodo; Nisful Laila (Jurnal Ekonomi Syariah Teori dan Terapan, 2016)
This research aims to see market reaction over the increasing and declining dividend announcement. The objective in this research is to test whether the stock price reacts positively to the increasing dividend announcement and reacts negatively to the declining dividend announcement are shown by the significant abnormal return (AR) value in around the announcement date and by the significant difference of abnormal trading volume activity (ATVA) before and after the announcement. The results indicate that market does not react over increasing as well as decreasing dividend announcement. This indicates that the event of dividend changes announcement are not reacted by market.